Profile of Allelochemical Compounds in Ratun Sorghum Leaf Extract (Sorghum bicolor L.) Based on GC-MS Analysis as a Bioherbicide Candidate - Edi Susilo (Agrovigor, 2026)
The intensive use of synthetic herbicides has led to environmental degradation and increasing weed resistance, highlighting the need for environmentally friendly alternatives. Sorghum is widely recognized as an allelopathic plant; however, information on the allelochemical profile of sorghum ratoon leaves remains limited. This study aimed to identify and interpret the allelochemical composition of sorghum ratoon leaf extract as a candidate for natural, allelopathy-based bioherbicides. An experimental approach was applied using ratoon leaf extracts obtained through stepwise maceration with n-hexane, ethyl acetate, and ethanol. Compound identification was performed using Gas Chromatography–Mass Spectrometry (GC-MS), and data were analyzed based on chromatographic peak areas and classified according to chemical structure and biological potential. The results revealed diverse secondary metabolites with allelopathic potential, including alcohols/phenolics, fatty acids, fatty acid esters, amides, sterols, steroids, triterpenoids, and organometallic compounds. Polar compounds, particularly alcohols and phenolics, were identified as the most promising candidates for water-soluble bioherbicides due to their high solubility and rapid absorption by weed tissues. Fatty acids, esters, and amides represented the dominant phytotoxic fractions, contributing to membrane disruption, oxidative stress, and metabolic interference. In contrast, non-polar compounds such as steroids and triterpenoids were less suitable for aqueous formulations but may function as supporting metabolites. Overall, sorghum ratoon leaves represent a promising source of allelochemicals for sustainable bioherbicide development.